BUDIDAYA MAGGOT BERBASIS EKONOMI SIRKULAR UNTUK MENDUKUNG KETAHANAN PANGAN - Anisa Kumala Sari; Didi Pramana; Putri Damayanti; Nanik Setyowati; Wuri Prameswari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The problem of organic waste in Indonesia is increasing along with population growth and changes in consumption patterns, leading to serious environmental impacts if not managed properly. One potential innovation to address this issue is the cultivation of maggots from Black Soldier Fly (BSF) larvae. Maggots have the ability to bioconvert organic waste into protein-rich biomass and residue (frass), which is beneficial as organic fertilizer. This study aims to analyze the role of maggot cultivation based on a circular economy in supporting food security, particularly through the provision of alternative feed and the utilization of frass in the agricultural sector. The research methods used are literature review and simple field experiments. The results show that out of 10 kg of organic waste used, 65% was successfully reduced. The resulting larval biomass reached 3.2 kg of fresh maggots (850 g dry), with a protein content of 42.7% and fat content of 27.5%, making it suitable as an alternative feed for fish and poultry. Furthermore, the residue in the form of frass amounted to 3.5 kg, which has the potential to be used as organic fertilizer containing macro-nutrients capable of improving soil fertility and crop productivity. In conclusion, maggot cultivation is an innovative solution for organic waste management as well as a sustainable strategy to strengthen food security. Through the principles of the circular economy, it can reduce waste, lower production costs, and increase the availability and affordability of food.